2016
DOI: 10.1186/s13023-016-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of late-onset Pompe disease and other muscle disorders by next-generation sequencing

Abstract: BackgroundLate-onset Pompe disease (LOPD) is a rare treatable lysosomal storage disorder characterized by progressive lysosomal glycogen accumulation and muscle weakness, with often a limb-girdle pattern. Despite published guidelines, testing for LOPD is often overlooked or delayed in adults, owing to its low frequency compared to other muscle disorders with similar muscle patterns. Next-generation sequencing has the capability to test concurrently for several muscle disorders. This could potentially lead to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 63 publications
0
36
1
2
Order By: Relevance
“…On the other hand, currently NGS-based strategies are largely adopted to study genetically heterogeneous conditions, including muscle diseases (14). Recent NGS data prove that 20-30% of myopathic patients carry causative mutations in genes typically not associated with the observed phenotype (16,(32)(33)(34). Many studies (32)(33)(34)(35)(36)(37) identified mutations in genes responsible for LOPD and other metabolic myopathies in patients with a wide range of phenotypes (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, currently NGS-based strategies are largely adopted to study genetically heterogeneous conditions, including muscle diseases (14). Recent NGS data prove that 20-30% of myopathic patients carry causative mutations in genes typically not associated with the observed phenotype (16,(32)(33)(34). Many studies (32)(33)(34)(35)(36)(37) identified mutations in genes responsible for LOPD and other metabolic myopathies in patients with a wide range of phenotypes (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that some of these commercially available gene panels are not necessarily designed to detect all deletion variants [15] or intronic pathogenic variants in the GAA gene, and thus may fail to detect them.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, next generation sequencing (NGS)-based panels have been shown to facilitate the diagnosis of LOPD [15,16]. Whole-exome sequencing (WES) is now routinely ordered in clinic for many conditions including undiagnosed causes of myopathy and neurological indications [1618], and has successfully diagnosed patients with Pompe disease [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ген, який кодує фермент GAA, картований на хромосомі 17q25.2-q25. 3., складається з 20 екзо-нів. Описані 360 мутацій, які спричиняють часткове або цілковите блокування каталітичної активності ферменту, зниження його стабільності та скорочен-ня періоду напіврозпаду [3].…”
Section: вступunclassified